Innovative approach for the synthesis of benzoxazine-modified montmorillonite. (August 2015) - Andronescu, C.; Garea, S. A.; Nicolescu, A.; Deleanu, C.; Eugeniu, V.; Iovu, H.
The synthesis of a benzoxazine (BZ) monomer inside the montmorillonite (MT) layers was done using a diamino-modified MT as the amine component, phenol, and formaldehyde. The formation of the BZ rings within the MT layers was investigated by thermogravimetric analysis, X-ray photoelectron spectroscopy, proton nuclear magnetic resonance spectroscopy, and X-ray diffraction, this being enhanced when dioxane was used as the solvent. The morphology of the hybrid BZ monomer was investigated by scanning electron microscopy.